Environment-sensitive fluorescent probes targeting mutant IDH1 for in vivo glioma imaging - Wenhua Li; Luning Song; Wenshuo Lv; Tao Xin; Deqing Sun; Wei Zhao (Analytica Chimica Acta, 2026)

Comparative toxicity of 6PPD and 6PPD-quinone on the gut-liver axis in zebrafish: Insights into microbiota dysbiosis and oxidative stress - Lipeng Liang; Hao Wang; Luning Cai; Jiaxin Liang; Xiaojun Niu; Xiaofei Song (Aquatic Toxicology, 2026)

Research Progress of Micro-mixing Technologies in Microfluidic Chips and Their Applications in Heavy Metal Detection in Seawater: A Review - Yuxuan Geng; Yanyong Liu; Longjiang Song; Junfei Wu; Ping Fu; Wenjie Zhao; Luning Jia; Yalin Yuan; Xueyong Liu (Thalassas: An International Journal of Marine Sciences, 2026)

The enrichment and source pathways of antibiotic resistance genes in leaf endophytes of organic vegetable mediated by light intensity - Yuzi Song; Jingxuan Liang; Luning Gong; Yu Wang; Di Zhang; Tailong Shi; Zhao Zhao (Plant and Soil, 2026)

Antibiotic reduction enhances the aggregation of intracellular and extracellular resistance genes in the phycosphere - Yu Wang; Di Zhang; Yuzi Song; Jingxuan Liang; Luning Gong; Zhao Zhao (Journal of Environmental Chemical Engineering, 2026)

Spatiotemporal Differences in Tectonic Deformation and Its Dynamic Mechanisms in the East China Sea Shelf Basin - Junlan Song; Yumao Pang; Chuansheng Yang; Yanqiu Yang; Luning Shang; Changqing Yang; Jing Sun (Journal of Ocean University of China, 2025)

Impact of phosphorus on the transfer of extracellular antibiotic resistance genes in water-sediment systems - Di Zhang; Jingxuan Liang; Yu Wang; Chao Xing; Yuzi Song; Ce Wang; Zikuo Liu; Xiaobin Yang; Luning Gong; Huijuan Shi; Zhao Zhao (Journal of Environmental Chemical Engineering, 2025)

Differences in Mesozoic–Cenozoic Structural Deformation Between the Northern and Southern Parts of the East China Sea Shelf Basin and Their Dynamic Mechanisms - Chuansheng Yang; Junlan Song; Yanqiu Yang; Luning Shang; Jing Liao; Yamei Zhou (Journal of Marine Science and Engineering, 2025)
The East China Sea Shelf Basin (ECSSB) and its adjacent areas, as key regions of the ocean–continent transition zone, have been affected by multiple complex plate collisions, subduction, and back-arc tension since the Mesozoic Era. The structural deformation provides a large amount of geological information on the ocean–continent transition zone. There are significant spatiotemporal differences in the structural deformation within the basin. However, the research remains insufficient and understanding is inconsistent, especially regarding the systematic study of the differences and dynamic mechanisms of north–south structural deformation, which is relatively lacking. This study is based on two-dimensional multi-channel deep reflection seismic profiles spanning the southern and northern basin. Through an integrated re-analysis of gravity, magnetic, and OBS data, the deformation characteristics and processes of the Meso-Cenozoic structures in the basin are analyzed. The differences in structural deformation between the southern and northern basin are summarized, and the controlling effects of deep crust–mantle activity and the influencing factors of shallow structural deformation are explored. Based on deep reflection seismic profiles, the structural deformation characteristics of the Yushan–Kume fault are revealed for the first time, and it is proposed that NW faults, represented by the Yushan–Kume fault, have important tuning effects on the north–south structural differential deformation in the ECSSB. The thermal subsidence of the lithosphere is the direct cause of the development of the Mesozoic ECSSB, while the subduction of the Paleo-Pacific plate is one of the important factors contributing to it. The combined effect of the two has led to significant differences between the northern and southern Mesozoic basin. During the Cenozoic Era, the alternating subduction and changes in the direction of subduction of the Pacific Plate led to spatiotemporal differences in structural deformation within the ECSSB. The development of NW faults was a key factor in the differences in structural deformation between the northern and southern basin. The study of structural deformation differences in the ECSSB not only deepens our understanding of the tectonic evolution in the East Asian continental margin region, but also has important significance for the exploration and evaluation of deep hydrocarbon resources in the ECSSB.

Microbial degradation of organophosphorus pesticides: novel degraders, kinetics, functional genes, and genotoxicity assessment - Bo Jiang; Nana Zhang; Yi Xing; Luning Lian; Yating Chen; Dayi Zhang; Guanghe Li; Guangdong Sun; Yizhi Song (Environmental Science and Pollution Research, 2019)

Correction to: Risk exposure assessment of per- and polyfluoroalkyl substances (PFASs) in drinking water and atmosphere in central eastern China - Zhibo Lu; Rong Lu; Hongyuan Zheng; Jing Yan; Luning Song; Juan Wang; Haizhen Yang; Minghong Cai (Environmental Science and Pollution Research, 2018)

Risk exposure assessment of per- and polyfluoroalkyl substances (PFASs) in drinking water and atmosphere in central eastern China - Zhibo Lu; Rong Lu; Hongyuan Zheng; Jing Yan; Luning Song; Juan Wang; Haizhen Yang; Minghong Cai (Environmental Science and Pollution Research, 2018)

Arsenic Trioxide and Icariin Show Synergistic Anti-leukemic Activity - Zhi Wang; Hong Zhang; Liling Dai; Tongguo Song; Ping Li; Yali Liu; Luning Wang (Cell Biochemistry and Biophysics, 2015)

Regulatory properties of malic enzyme in the oleaginous yeast, Yarrowia lipolytica, and its non-involvement in lipid accumulation - Huaiyuan Zhang; Luning Zhang; Haiqin Chen; Yong Q. Chen; Colin Ratledge; Yuanda Song; Wei Chen (Biotechnology Letters, 2013)